Pelatihan Keterampilan Anyaman Rotan bagi Ibu-Ibu PKK Desa Takaras Kecamatan Manuhing - Saiffullah Darlan; Yesni Nopy (Universitas Lancang Kuning, 2022)
This community activity seeks to offer motivation and skills to mothers of Family Welfare Education students in Takaras Village, Manuhing District, so they may learn to make woven rattan items. As a result, the outcomes can boost the economic selling value and well-being. Counseling and training are used to give training learning approaches. Counseling is the distribution of information and talks, whereas training entails learning how to weave good rattan that can be sold profitably. Adult learning patterns, such as lectures, conversations, and practice, are used to carry out the technique. The training was effective, even though it was still simple since the mothers of Family Welfare Education could make use of the readily available rattan, which could be turned into completed items such as bags, lawung, and mats.